KONSEP PENDIDIKAN ISLAMIC ENTERPRENEURSHIP DALAM MENGEMBANGKAN KETERAMPILAN BERWIRAUSAHA PERSPEKTIF IMAM AL-GHAZALI - Bunaya; Muhtadi Abdul Mun'im (LP2M IAIN Sultan Amai Gorontalo, 2025)
Education as a whole through spiritual, intellectual and moral aspects in going beyond the mastery of knowledge alone. The ideal educational goal includes the practice of knowledge for the welfare of society and divine pleasure. The implementation of Islamic entrepreneurship emphasizes fair leadership based on Islamic values and maintains a balance between profitability and social sustainability. As for the qualitative research method with a library research approach, research whose subject is literature and literature, 'Ihya' Ulum Ad-Din' is the source. Researchers with classical text analysis are very relevant to literature research that only focuses on obtaining data and information through books by Imam Al-Ghazali. The analysis data found regarding the concept of Islamic entrepreneurship education includes, that the purpose of entrepreneurship is to worship, and to balance between the world and the hereafter, so that always remember that everything is entrusted, while ethics in business include honesty, justice that does not harm others and responsibility in all interactions. The values of Islamic ethics include, halal intentions and goals in charity, carrying out fardhu kifayah, paying attention to the afterlife market when carrying out activities in the market, keeping away everything that is doubtful and has haram elements and the like, so that always introspective oneself in entrepreneurship with full trust and responsibility. Entrepreneurial skills also include an optimistic attitude in running their business, building a good mentality in facing all challenges, forming practical skills in self-management and discipline, tawakal and optimism as well as building a sustainable entrepreneurial mentality and the integration of Islamic education in the entrepreneurship curriculum.